A Comparative Study of Psychiatric Disorders among Mothers of Children with Chronic Diseases and Mothers of Healthy Children - Zohreh Eskandari Shahraki, Mohammad Efffatpanah, Serajaddin Gray, Mitra Radfar, Mehdi Rezaei, Hamidreza Hekmat, Shokofeh Radfar (Journal of Applied Pharmaceutical Science, 2017)
The current study was conducted to compare the psychiatric disorders in mothers of children with a chronic disease with mothers of healthy children. The study was observational-analytical case-control study. The study population included mothers of chronically ill children who were hospitalized in internal wards of the Tehran Children Medical Center and mothers of normal children who referred to the Dental Clinic of this center. For sampling, convenience sampling method was used and127 mothers were selected (65 mothers of healthy children and 62 mothers of ill children). The instrument used was SCL-90-R and demographic questionnaires. The collected data were analyzed using descriptive statistics and multivariate analysis of variance. The results showed that mothers of children with chronic disease had a significant difference in all components of psychiatric disorders (P
Keywords: Psychiatric disorders, quality of life, chronic diseases of children.